Clinical evidence for washing and cleansers in acne vulgaris: a systematic review*. (3rd October 2018) - Stringer, Thomas; Nagler, Arielle; Orlow, Seth J.; Oza, Vikash S.
Abstract: Purpose: Washing and over-the-counter cleansers are common interventions in acne vulgaris (AV), but the clinical evidence for their benefit is poorly understood. This systematic review presents clinical studies of washing and cleanser efficacy in acne vulgaris to guide treatment recommendations of dermatologists. Materials and methods: We surveyed English-language articles indexed in MEDLINE (1951–March 2017) and EMBASE (1974–March 2017). Articles were required to be prospective studies of a single over-the-counter cleanser or washing intervention in AV with an objective AV outcome measurement published in a peer-reviewed journal. Results and conclusions: Fourteen prospective studies representing 671 participants were included in this review. Modalities investigated included face washing frequency, true soap/syndet cleansing bars, antiseptic cleansers, alpha and beta-hydroxy (i.e. salicylic) acid cleansers, and several proprietary formulations. Given the low number of well-performed clinical studies of cleansers and washing, it is difficult to formulate reliable recommendations. We hope that our findings highlight the necessity of further investigation in this area.